Contagion pattern identification through minimum spanning trees during the Asian financial crisis - Vasile-George Marica (Financial Studies, 2019)
Complexity in financial markets is slowly overwhelming canonical statistical modelling. With global crises which stemming from contagion effects becoming more frequent, new tools for financial distress transmission c apture are needed. Graph theory , with its branch on minimum spanning trees can help researchers better represent the numerous multivariate and asynchronous interactions that suddenly manifest during moments of market panic. Under the current research, a no vel graphical methodology is em ployed for the description of the 1997 Asian financial crisis. It is shown that market sentiment can have an interpretable image through the use of correlation based minimum spanning trees, a useful tool for policy makers and risk managers alike.
Keywords: C10; C18; C14; C38; C88; 330; correlation matrix; graph theory; minimum spanning tree